'Love, Let Me Some Senseless Piece of This Place Be': Landscape, Body, and the 'Creature of Place' in Donne's Songs and Sonnets. (1st December 2016) - Hegedüs, Kader N.
Abstract : This article reconsiders the function John Donne (1572–1631) attributes to tangible landscapes and environments in his Songs and Sonnets . Inscribing these metaphors within wider considerations on Donne's spatial imagination, I suggest that traditional criticism has been privileging his fascination towards the scientific discoveries of his times and their emphasis on rather abstract ideas of spatiality (cosmology, cartography, microcosmic and macrocosmic relations), while neglecting for the most part occurrences of 'placial' components – with the precise landscapes that they presuppose – in his love poetry. A closer look at poems such as 'The Bait' 'Twickenham Garden' or 'The Blossom', however, highlights Donne's approach to the intricate relationship his characters seem to entertain with the environment they occupy. Mostly articulated in terms of corporeal transformations and divisions, these poems stress how lovers tend to become a 'creature' of the place they occupy, and the resulting tensions that arise between body and mind. This article concludes by suggesting that these 'placial' metaphors actually legitimate and invoke the 'spatial' flexibility, generally favoured by critics, one can observe in the other poems where Donne's characters succeed in resolving these tensions.